Similar Material Simulation Study on Protection Effect of Steeply Inclined Upper Protective Layer Mining with Varying Interlayer Distances - Zhigang Yuan; Yaohua Shao; Zhuohui Zhu (Advances in Civil Engineering)
Protective layer mining, as a dominating regional prevention measure, is generally adopted to prevent and control gas disasters in highly gassy or outburst mines of China. Interlayer distance is one of the most important factors that influences protection effect. However, how does interlayer distance affect the protection effect of steeply inclined upper protective layer mining is not understood fully. According to the engineering practice in Nantong mining district, a new method for similar material simulation experiment of steeply inclined upper protective layer mining is proposed, in which an orthogonal test of similar materials comprising of sand, cement (containing gypsum and fly ash), and water mixture is conducted to obtain relations between proportioning parameters and mechanical properties using a multiple regression method. And then the method is applied to study the protection effect of steeply inclined upper protective layer mining with varying interlayer distances. The results show the following. (1) The proportioning parameters of similar material have strong linear relations with its mechanical properties, and mechanical behaviors of such similar material denote that it can simulate most coal-rock lithologies in coal mine. (2) Both pressure-relief curves and swelling strain curves for protected layer present convex shapes; protection angles at lower excavation boundary are greater than those of upper excavation boundary; with the increase of interlayer distance, the pressure-relief curve evolves from pattern “∩” to pattern “∧” and corresponding pressure-relief region becomes narrower, the center of pressure-relief region tends to transfer to the corresponding center of upper protective layer excavation region, the stress concentration coefficient decreases, the protection angles change little, and the length of the protection region reduces dramatically. (3) The protection region and protection angle calculated based on swelling strain of 3‰ are less than the empirical values based on the dip angle in Provisions, denoting that the method proposed in this study is safer than that in Provisions. The research results provide a useful guide for layouts of roadway and gas drainage boreholes to prevent gas disaster in Nantong coal mine district.